A New Framework for the Assessment of Cerebral Hemodynamics Regulation in Neonates Using NIRS (2016)
We present a new framework for the assessment of cerebral hemodynamics regulation (CHR) in neonates using near-infrared spectroscopy (NIRS). In premature infants, NIRS measurements have been used as surrogate variables for cerebral blood flow (CBF) in the assessment of cerebral autoregulation (CA). However, NIRS measurements only reflect changes in CBF under constant changes in arterial oxygen saturation (SaO2). This condition is unlikely to be met at the bedside in the NICU. Additionally, CA is just one of the different highly coupled mechanisms that regulate brain hemodynamics. Traditional methods for the assessment of CA do not take into account the multivariate nature of CHR, producing inconclusive results. In this study we propose a newly developed multivariate methodology for the assessment of CHR. This method is able to effectively decouple the influences of SaO2 from the NIRS measurements, and at the same time, produces scores indicating the strength of the coupling between the systemic variables and NIRS recordings. We explore the use of this method, and its derived scores, for the monitoring of CHR using data from premature infants who developed a grade III-IV intra-ventricular hemorrhage during the first 3 days of life.